FIRST REPORT OF EARLY TRIASSIC A-TYPE GRANITE AND SYENITE INTRUSIONS FROM TAIMYR: PRODUCT OF THE NORTHERN EURASIAN SUPERPLUME? - Vernikovsky V.A.; Vernikovskaya A.E.; Travin A.V.; Pease V.L.; Romanov A.P.; Gee D.G. (My University, 2003)
Ion-microprobe U–Th–Pb analyses of zircon from three high-level syenite–granite stocks in the western part of the Taimyr fold-and-thrust belt have yielded early Triassic ages of 249–241 Ma. Those syenite–granite bodies intrude unmetamorphosed late Paleozoic to early Mesozoic terrigenous and volcanic supracrustal rocks, including the early Triassic Siberian traps. 40Ar–39Ar isotopic ages of 245–233 Ma correlate well with the ion-microprobe data and define the time of closure for the K–Ar isotopic system. Limited geochemical data for the early Triassic syenite–granite plutons show that they have metaluminous compositions, high potassium, high REE and high LIL concentrations, and 87Sr/86Sr and εNd ratios intermediate between crust and mantle, suggesting a hybrid mantle–crustal origin. We tentatively suggest that they formed in an anorogenic setting as a result of the Permo-Triassic Euroasian superplume.
Keywords: Arctic Siberia; Taimyr; Early Triassic; Plume magmatism; Syenite– granite; U–Pb and Ar –Ar geochronology; Mesozoic::Triassic; Мезозой::Триасовая